Foolish Love: Exploring the Theme of Love and Madness in "Love Not Times Fool" (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Prof. Vikas Sharma’s Love’s Not Time’s Fool is a bold and thought-provoking literary exploration of love’s fragile essence in the chaotic rhythm of postmodern life. Penned during the COVID-19 pandemic a period marked by isolation, introspection, and emotional volatility the novel delves deep into the shifting topography of human desire, intimacy, and connection in a society increasingly veering towards transactional gratification and moral ambiguity.At the heart of the narrative stands Richa Pandit, a fiercely intelligent and emotionally layered protagonist whose journey through extramarital entanglements, casual liaisons, and moments of same-sex intimacy lays bare the inner dissonance between bodily fulfillment and emotional hunger. Through Richa’s nuanced experiences and her emotionally fraught relationship with Abhilash, the novel excavates the psychological vacuum and existential loneliness that often masquerade as freedom in contemporary relationships.Yet, beneath this gritty portrayal of fleeting desires and relational dissonance, the novel champions the redemptive power of love a love not immune to folly, but enriched by it. The title itself, echoing Shakespeare’s sonnet, serves as a lyrical contradiction: while time tests, erodes, and often mocks affection, true love, in its most foolish and unguarded form, dares to defy temporality. It is in this foolishness—this willingness to hope, to trust, and to feel despite the odds—that the novel finds its most profound wisdom.